Respuesta :

Answer:

Step-by-step explanation:

[tex](\sqrt{z} +\sqrt{22})(\sqrt{z} -\sqrt{22})=35[/tex]

Subtract both sides from 35

[tex](\sqrt{z}+\sqrt{22} (\sqrt{z} -\sqrt{22})-35=35-35[/tex]

Simplify:

[tex](\sqrt{z})^{2} -57=0[/tex]

Factor [tex](\sqrt{z})^{2} -57: (\sqrt{z}+\sqrt{57}) (\sqrt{z}-\sqrt{57})[/tex]=0

[tex]\sqrt{z} +\sqrt{57}=0 or \sqrt{z} -\sqrt{57}=0[/tex]

[tex]\sqrt{z} +\sqrt{57} =0: No Solution for Z[/tex]

[tex]\sqrt{z} -\sqrt{57} =0: z=57[/tex]

Your answer will be z=57

and No solution

Answer:

(

z

+

22

)(

z

22

)=35

Subtract both sides from 35

(\sqrt{z}+\sqrt{22} (\sqrt{z} -\sqrt{22})-35=35-35(

z

+

22

(

z

22

)−35=35−35

Simplify:

(\sqrt{z})^{2} -57=0(

z

)

2

−57=0

Factor (\sqrt{z})^{2} -57: (\sqrt{z}+\sqrt{57}) (\sqrt{z}-\sqrt{57})(

z

)

2

−57:(

z

+

57

)(

z

57

) =0

\sqrt{z} +\sqrt{57}=0 or \sqrt{z} -\sqrt{57}=0

z

+

57

=0or

z

57

=0

\sqrt{z} +\sqrt{57} =0: No Solution for Z

z

+

57

=0:NoSolutionforZ

\sqrt{z} -\sqrt{57} =0: z=57

z

57

=0:z=57

Your answer will be z=57